2019
DOI: 10.1111/pere.12268
|View full text |Cite
|
Sign up to set email alerts
|

Commitment in relationships: An updated meta‐analysis of the Investment Model

Abstract: This article provides a systematic review and updated meta‐analysis of the extant literature on Rusbult's Investment Model of Commitment. This meta‐analysis aimed to determine the strength of the associations between commitment and its antecedents and to investigate potential moderators of these associations. This meta‐analysis included 50,427 participants from 202 independent samples (collected between 1980 and early 2016) that had examined the intercorrelations between satisfaction, investment size, quality … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(45 citation statements)
references
References 50 publications
(75 reference statements)
2
36
0
Order By: Relevance
“…Commitment to the mentoring relationship was measured using an adapted version of the Investment Model Scale (Rusbult et al, 1998), which was originally developed for application to romantic relationships and has been successfully used in a variety of settings (Le & Agnew, 2003; Tran et al, 2019) including a recent adaptation for adults mentoring youth (Gettings & Wilson, 2014). Commitment was measured using four items (e.g., “I am determined to make my relationship with my mentee successful”) rated on a 5‐point scale (1 = Strongly Disagree to 5 = Strongly Agree ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Commitment to the mentoring relationship was measured using an adapted version of the Investment Model Scale (Rusbult et al, 1998), which was originally developed for application to romantic relationships and has been successfully used in a variety of settings (Le & Agnew, 2003; Tran et al, 2019) including a recent adaptation for adults mentoring youth (Gettings & Wilson, 2014). Commitment was measured using four items (e.g., “I am determined to make my relationship with my mentee successful”) rated on a 5‐point scale (1 = Strongly Disagree to 5 = Strongly Agree ).…”
Section: Methodsmentioning
confidence: 99%
“…Theory and empirical evidence suggest that the benefits of youth mentoring, in areas such as increased academic engagement, reduced risk‐taking, and improved family and peer relationships (e.g., Deutsch, Reitz‐Krueger, Henneberger, Futch Ehrlich, & Lawrence, 2017; Grossman & Rhodes, 2002; Grossman & Tierney, 1998; Herrera, DuBois, & Grossman, 2013; Herrera, Grossman, Kauh, & McMaken, 2011; Parra, DuBois, Neville, Pugh‐Lily, & Povinelli, 2002; Wheeler, Keller, & DuBois, 2010), are achieved within the context of a strong, consistent relationship with a supportive mentor over time (Karcher, 2005; Parra et al, 2002; Rhodes, 2002, 2005; Rhodes, Spencer, Keller, Liang, & Noam, 2006; Spencer, 2007a). Commitment, which reflects a person's intention to sustain and remain psychologically attached to a relationship (Rusbult, 1980; Rusbult, Martz, & Agnew, 1998), provides an important indicator of the likelihood that someone will choose to continue or terminate a relationship across a wide variety of interpersonal relationships (e.g., Le & Agnew, 2003; Rusbult, 1980; Rusbult & Martz, 1995; Rusbult et al, 1998; Tran, Judge, & Kashima, 2019). According to Rusbult's (1980) Investment Model, commitment to the relationship is predicted by satisfaction with the relationship (i.e., weighing the costs and benefits of the relationship and comparisons to past relationship experiences and expectations for an ideal relationship), investment (the magnitude and importance of what has been put into the relationship that would be lost or lose value if the relationship were to end, including both intrinsic and extrinsic investments), and available alternatives (i.e., the availability and desirability of other potential mentees or not having a mentoring relationship).…”
Section: Relationship Commitmentmentioning
confidence: 99%
“…The decision to move in with a romantic partner is often made with little conscious deliberation (Lindsay, 2000;Manning & Smock, 2005;Sassler, 2004;Stanley et al, 2006). Such investments, in turn, serve as barriers to relationship dissolution (Le & Agnew, 2003;Rusbult, 1980;1983;Tran et al, 2019). The decision to end a relationship tends to be highly effortful and difficult (Dailey et al, 2009;VanderDrift et al, 2009), even when the relationship is unhealthy or even abusive (Arriaga, 2002;Arriaga, 2013;Rusbult & Martz, 1995).…”
Section: Discussionmentioning
confidence: 99%
“…A large body of longitudinal work supports this model. For example, a meta-analysis of 202 samples ( N = 50,427) found that alternatives and investment emerged as independent predictors of commitment, above and beyond relationship satisfaction ( Tran et al, 2019 ). Commitment, in turn, is a strong predictor of choosing to remain in the relationship ( Le & Agnew, 2003 ).…”
Section: Emerging Evidence Of a Progression Biasmentioning
confidence: 99%